2000
DOI: 10.1681/asn.v1161093
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Low Bone Turnover and Occurrence of Osteomalacia after Kidney Transplantation

Abstract: Abstract. Kidney transplantation corrects most of the metabolic abnormalities that cause renal osteodystrophy. However, many transplanted patients develop osteoporosis and other bone lesions that are related, at least in part, to their immunosuppressive regimen. The precise histologic patterns of bone disease after transplantation are not well defined. In a study designed to investigate this issue, 57 adult posttransplant patients agreed to undergo bone biopsies and blood drawings. There were 32 men and 25 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…While earlier studies reported substantial bone loss in the first year post-transplantation ( Julian et al, 1991 ; Heaf, 2003 ), stability of trabecular bone mass is a consistent finding in contemporary kidney transplant recipients ( Iyer et al, 2014 ; Evenepoel et al, 2020 ; Evenepoel et al, 2017 ; Marques et al, 2019 ). As several studies demonstrated a relationship between cumulative steroid dose and post-transplantation bone loss ( Evenepoel et al, 2017 ; Monier-Faugere et al, 2000 ; Parker et al, 1999 ; Rojas et al, 2003 ), the introduction of steroid minimization protocols has been proposed as an explanation for this beneficial trend ( Iyer et al, 2014 ; Kidney Disease: Improving Global Outcomes (KDIGO) CKD-MBD Update Work Group, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While earlier studies reported substantial bone loss in the first year post-transplantation ( Julian et al, 1991 ; Heaf, 2003 ), stability of trabecular bone mass is a consistent finding in contemporary kidney transplant recipients ( Iyer et al, 2014 ; Evenepoel et al, 2020 ; Evenepoel et al, 2017 ; Marques et al, 2019 ). As several studies demonstrated a relationship between cumulative steroid dose and post-transplantation bone loss ( Evenepoel et al, 2017 ; Monier-Faugere et al, 2000 ; Parker et al, 1999 ; Rojas et al, 2003 ), the introduction of steroid minimization protocols has been proposed as an explanation for this beneficial trend ( Iyer et al, 2014 ; Kidney Disease: Improving Global Outcomes (KDIGO) CKD-MBD Update Work Group, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of age, gender, PTH, and CyA on bone volume and bone turnover were ignored by the prominent effects of glucocorticoids. The prevalence of mineralization defect in the presence of normal serum levels of calcidiol and calcitriol suggests vitamin D resistance [ 42 ]. Ulivieri F, et al, 2002 showed that in twenty KTx male patients received one of two regimens (CyA combined with methylprednisolone with or without azathioprine).…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies revealed that the risk factors involved low BMD post-KTx include increasing age, time after transplant, gender, and ethnicity [ 71 , 72 , 73 , 74 ]. Another study showed that the effects of age, gender, PTH, and CyA on bone density and bone turnover are masked by the prominent effects of steroids [ 42 ]. However, Aroldi and colleagues investigated the effects of immunosuppressive regimens on vertebral BMD in KTxR and revealed that the lumbar BMD decreased significantly in KTxR given CyA with steroids compared to those under CyA alone [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding osteoporosis, the use of GCs remains the key risk factor for the development of this type of bone disease. An early post-RTx time is characterised by a rapid loss of bone mass that mainly affects trabecular bone due to intensive GC regimens ( 44 ). The GCs inhibit osteoblast proliferation and differentiation and stimulate apoptosis of both osteoblasts and osteoclasts.…”
Section: Mineral and Bone Disorder In Rtxmentioning
confidence: 99%